The Strengthening Character Education (PPK) Using Illustrated Media on the WhatsApp Application in Elementary School - Elisabeth Lamba; Abdul Rahman (EduLine: Journal of Education and Learning Innovation, 2023)
This study aims to explore the extent to which the character education program through visual media in the WhatsApp application is effective for higher grade levels in the elementary school. The goal is to strengthen character education in accordance with the principles of law. The method of this research uses a qualitative approach with a case study design to explore the phenomenon under investigation. Data was collected from both teachers and a select group of students through in-depth interviews. The process of enhancing character education at SDN 7 Rindingallo comprises three key phases: planning involving a student needs analysis, curriculum assessment, character value selection, and the creation of discussion spaces both offline and online; implementations which includes sharing images/videos depicting character values before lessons, collaborating with school principals and parents; evaluation and monitoring, employing tests and attitude journals. Nevertheless, the implementation of Character Education through visual media on the WhatsApp application has encountered challenges, primarily due to limited internet availability and insufficient parental or familial support. To address these issues, solutions have been proposed, such as providing teachers with Indihome WiFi access and encouraging students to study with peers who have data access while actively engaging in conversations to educate parents and garner their support for the character education program